QRS fragmentation: its role in sherlocking the arrhythmogenic heart - Hafeez Ul Hassan Virk; Salman Farooq; Ali Raza Ghani; Shilpkakumar Arora (Greater Baltimore Medical Center, 2016)
The electrocardiogram (ECG) is a commonly available basic diagnostic modality in in-patient, out-patient, and emergency departments. In patients with coronary artery disease (CAD), the presence of a fragmented QRS (f-QRS), which is an extra R wave (R'), notching of the single R wave, notching of the S wave in at least two contiguous leads on the 12-lead ECG, is associated with a myocardial scar from previous myocardial injury. Furthermore, the presence of f-QRS has been shown to be associated with adverse outcomes in CAD and non-CAD patients. In the present paper, we will solely focus on the usefulness and utilization of f-QRS in predicting ventricular tachyarrhythmia in many heart diseases, that is, ischemic cardiomyopathy, non-ischemic cardiomyopathy, hypertrophic obstructive cardiomyopathy, Brugada syndrome, and arrhythmogenic right ventricular cardiomyopathy. In the majority of such cases, ventricular tachyarrhythmia results in sudden cardiac death. Diagnosing them beforehand can lead to prevention and/or early treatment of these arrhythmias to prevent potential morbidity and mortality.